Rain Attenuation Modelling and Mitigation in The Tropics: Brief Review - Abayomi Isiaka Yussuff; Nor Hisham Khamis (Institute of Advanced Engineering and Science, 2012)
This paper is a brief review of Rain AttenuationModelling and Mitigation in the Tropics. The fast depleting availability of the lower frequency bands like the Ku-band as a result of congestion by commercial satellite operations coupled with severe rain attenuations experienced at higher frequency bands (Ka and Q/V), particularly in the tropical regions which was caused by higher rainfall rates and bigger raindrop size, amongst others; it was pertinent that deliberate effforts be geared towards research along this direction. This became even more critical owing to a dearth database along the slant path in the tropical regions for use in rain propagation studies at microwave frequencies, especially at millimeter wave bands (where most signal depolarization and fading takes place). The results presented in this work are valuable for design and planning of the satellite link, particularly in the tropical regions.DAH, ITU-R and SAM model simulations along the slant-path were investigated using local rainfall data at 0.01% of the time, while making use of TRMM data from NigComSat-1 satellite to obtain the measured data for Lagos. Terrestrial attenuation data for 0.01% of the time for UTM were obtained from the UTM wireless communication center (WCC). The attenuation data were thereafter transformed to slant path using transformation technique proposed for Ku band byA. Y. Abdulrahman. Theattenuation exceeded for other percentages of the average year was obtained using statistical interpolation extrapolation method.It was observed that the proposed model predicts creditably well for the ka down link frequency band, by producing the best performance when compared with SAM, DAH and ITU-R models.DOI:http://dx.doi.org/10.11591/ijece.v2i6.1222